Phonetic features of Chinese in teaching students at the Institute of languages and culture of the peoples of North-Eastern of the Russian Federation - Prokopeva Amalia; Zakharova Galina (SHS Web of Conferences, 2022)
The purpose of the article is to develop students’ personal qualities, as well as the formation of universal, general professional and professional competencies in accordance with the requirements of the Federal State Educational Standard of Higher Education in the direction of 44.03.05 Teacher Education (two training profiles). Native language (Yakut) and the literature and the foreign language (Chinese) training. The task is to provide the highly qualified teachers with a high level of professional and social competence, proficient in the specifics of intercultural communication and foreign languages, in particular Chinese, through innovative technologies, methods, and creative practices.